Comparison of hair dye preparations from red dragon fruit skin extract (Hylocereus polyrhizus) for artistic hair coloring - Situmorang, Izti Zaura Putri Br; Efrianova, Vivi (PT The Collaboration UVW, 2024)
This research aimed to analyze the comparative results of cosmetic formulas of natural hair dye from dragon fruit skin through a maceration extraction process with formulations of 15%, 30%, and 45% as assessed through pH tests (laboratory tests), organoleptic tests, Hedonic test (panelists’ preferences) and color stability tests. This research used a quantitative approach with an experimental research design. The data in this research used primary data. Data were collected through observation, documentation, and questionnaires. The research instrument used questionnaires to collect organoleptic test data of dragon fruit skin extra hair dye preparations. The data were analyzed using normality, homogeneity, and ANOVA tests. A comparison of hair dye preparations of red dragon fruit peel extract showed that F1, F2, and F3 dye preparations had pH levels of 11, 10, and 11. The texture on F1 was 43% fine-textured, on F2 it was 57% fine-textured, and on F3 43% was very fine-textured. The aroma on F1 was 43% quite scented dragon fruit skin, on F2 43% was quite scented dragon fruit skin and on F3 57% was quite scented dragon fruit skin. The color in F1 was 43% not purplish red, in F2 29% less colored and not purplish red, and in F3 29% in very colored, colored and not purplish red. There was no significant difference in the comparison results of making natural hair dye preparations of red dragon fruit peel extract (Hylocereus polyrhiuzus).